2015
DOI: 10.21149/spm.v57s2.7598
|View full text |Cite
|
Sign up to set email alerts
|

“Dame una pastilla”: los significados del VIH/sida en la práctica del bareback en la ciudad de México e implicaciones para la prevención

Abstract: S113salud pública de méxico / vol. 57, suplemento 2 de 2015 Significados asociados con el bareback en MéxicoArtículo originAl "Dame una pastilla": los significados del VIH/sida en la práctica del bareback en la ciudad de México e implicaciones para la prevenciónSilvia Magali Cuadra-Hernández, PhD, (1) Ricardo Baruch-Domínguez, MSP,César Infante, PhD, (1) José Arturo Granados-Cosme, PhD.(1 AbstractObjective. To analyze and understand the meanings that gay men in Mexico City associate to unprotected sex such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…The results showed that both the alcohol/marijuana and poly-user classes were significantly more likely to engage in sex under the influence of drugs and alcohol. In Mexico, a study found that MSM engaging in CAS behaviors was due to a change in risk perception, with access to antiretroviral therapy [ 47 ]. Different studies in Mexico have shown growing concern for addiction to crystal meth as a particular drug that may potentiate new cases of HIV among MSM due to its potential to enhance sexual desire and CAS with multiple partners [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that both the alcohol/marijuana and poly-user classes were significantly more likely to engage in sex under the influence of drugs and alcohol. In Mexico, a study found that MSM engaging in CAS behaviors was due to a change in risk perception, with access to antiretroviral therapy [ 47 ]. Different studies in Mexico have shown growing concern for addiction to crystal meth as a particular drug that may potentiate new cases of HIV among MSM due to its potential to enhance sexual desire and CAS with multiple partners [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Algunos autores indican que la inconsistencia en el uso del condón está relacionada con lo que se ha denominado la "fatiga de la prevención" (Cuadra Hernández et al, 2015;Santiesteban Díaz et al, 2019;Sola Lara et al, 2021) y el habitus de resistencia (Crossley, 2004). La primera se refiere a la existencia de un cansancio y apatía de las poblaciones clave frente a los mensajes tradicionales del uso del condón y la desconexión entre los significados de las personas y los que se tramitan a través de dichos mensajes.…”
Section: Factores De Vulnerabilidadunclassified